Four lectures on ethics : anthropological perspectives - Lambek, Michael; Das, Veena; Fassin, Didier; Keane, Webb, 1955- (Masterclass series (Chicago (Ill.)), 2015)
Anthropology has recently seen a lively interest in the subject of ethics and comparative notions of morality and freedom. This masterclass brings together four of the most eminent anthropologists working in this field--Michael Lambek, Veena Das, Didier Fassin, and Webb Keane--to discuss, via lectures and responses, important topics facing anthropological ethics and the theoretical debates that surround it. The authors explore the ways we understand morality across many different cultural settings, asking questions such as: How do we recognize the ethical in different ethnographic worlds? What constitutes agency and awareness in everyday life? What might an anthropology of ordinary ethics look like? And what happens when ethics approaches the political in both Western and non-Western societies. Contrasting perspectives and methods- and yet in complimentary ways- this masterclass will serve as an essential guide for how an anthropology of ethics can be formulated in the twenty-first century.